IMPACT OF BRITISH COLONIALISM ON THE ỌDIONWERE CONFLICT MANAGEMENT INSTITUTION IN BENIN KINGDOM, NIGERIA (Glocalism: Journal of Culture, Politics and Innovation, 2024)
This study examines the profound impact of British colonialism on the Odionwere conflict management institution in Benin Kingdom, Nigeria. Before the colonial intervention, the Odionwere played a crucial role in resolving disputes and maintaining social harmony within the community. However, the advent of British colonial rule in the late 19th century significantly changed traditional governance structures. The imposition of indirect rule by the British colonial administrators altered the Benin Kingdom’s power dynamics, marginalizing the Odionwere’s authority. The establishment of colonial courts and the introduction of Western legal systems further undermined the traditional conflict resolution mechanisms. This study explores how the Odionwere, once central to dispute resolution, experienced a decline in influence and autonomy as colonial policies reshaped the socio-political landscape. By meticulously analyzing archival documents, oral histories, and ethnographic data, this research contributes to understanding the intricate interplay between colonialism and Indigenous institutions, shedding light on the lasting repercussions of colonial policies on local governance structures and conflict resolution practices in the Benin Kingdom.
Keywords: Colonialism; Ọdionwere; Conflict Management; Benin Kingdom; Nigeria